AIRCRAFT MAINTENANCE MARKET IN UKRAINE, ANALYSIS OF THE STATE PROBLEMS OF REFORMATION - Orlov Philip О. (Proceedings of National Aviation University (archive), 2008)
Maintenance market qualitative change and main problems of its reformation are analyzed.